Pendekatan Psikoedukasi dalam Mencegah Kecanduan Gadget pada Siswa Kelas 9 di SMPN 45 Semarang - Siti Hikmah; Siti Robaiyani; Hygidia Rizqia Novika; Yogi Rahmadani (Jurnal Kemitraan Masyarakat, 2024)
The development of technology makes daily activities easier. However, at the same time it can also have negative impacts, one of which is gadget addiction. Currently, many teenagers have grown up along with the development of gadgets since early age. This makes them accustomed to using gadgets in their daily lives. However, if used excessively, it can cause gadget addiction. From the sample of student assessment results from SMPN 45 Semarang, students were found to be indicated as being addicted to gadgets. Therefore, researchers took the initiative to conduct an intervention in the form of psychoeducation to educate teenagers about gadget addiction. Based on the results of the pretest and posttest analysis, an increase in knowledge related to gadget addiction was found with a significance value of 0.000 <0.05. These results indicate that intervention in the form of psychoeducation can successfully increase adolescent knowledge related to gadget addiction